Epidemiological Profile of the Pathologies of the Oral Cavity in a Peruvian Population: A 9-Year Retrospective Study of 18,639 Patients - Ángelo Sabogal; Jhonn Asencios; Ada Robles; Eloy Gamboa; José Rosas; Jorge Ríos; Frank Mayta-Tovalino (The Scientific World Journal)
Aim. To determine the epidemiological profile of oral diseases in a marginal urban Peruvian population. Methods. A 9-year retrospective study was conducted, analysing 18,639 clinical records from the María Auxiliadora Hospital between 2006 and 2015 with diagnoses of oral lesions using ICD-10 criteria. Clinical records were analysed for sex, tumour, periapical abscess and sinus, cysts of the oral region, other lesions of the oral mucosa and cavity, gingivitis and periodontal disease, dentofacial anomalies, diseases of pulp, etc. Results. Of 18,639 cases, the prevalence was higher in women for the following pathologies: unspecified dental caries (30.6%); impacted tooth in the category of disorders of tooth development and eruption (2.0%); pulpitis (6.8%) in the category of diseases of pulp and periapical tissues; temporomandibular joint (TMJ) disorders (1.5%) in the category of dentofacial anomalies; acute gingivitis (7.5%); radicular cyst (0.3%) in the category of cysts of the oral region; and periapical abscess without sinus (2.0%). Conclusions. We found a significant association between sex and different types of dental caries, disturbances in tooth eruption, diseases of pulp and periapical tissues, and dentofacial anomalies. The study also shows a statistically significant association between sex and gingivitis, periodontal disease, and periodontal abscess and sinus.